Teori-Teori Belajar & Pembelajaran - Muhamad Syaifudin Ahyar; Nisrina; Badrus Zaman (Yayasan Al-Afif, 2025)
This study examines the concepts of learning and teaching, along with foundational theories, including behaviorism, cognitivism, constructivism, and humanism, due to their crucial role in shaping students' behavior and thinking patterns. The research uses a library research method with documentation techniques from relevant literature. Findings indicate that learning theories provide a conceptual framework for understanding the learning process, assisting teachers in designing and managing instruction effectively, and adapting strategies to students’ characteristics. These results highlight the importance of applying learning theories as a basis for meaningful and student-centered educational practices